Considerations about the rainfall, topography and soils and the analysis of potential of agricultural expansion in the Northern Mozambique region - Macarringue, Lucrêncio Silvestre; Sano, Edson Eyji; Chaves, Joselisa Maria; Bolfe, Edson Luis (Sociedade & Natureza, 2017)
2009, it was implemented a trilateral cooperation program among Mozambique, Brazil and Japan calledProSAVANA in the northern region of Mozambique (Nacala Corridor). The objectives of this study are:to characterize the conditions of precipitation, topography and soils of this region; and to analyze thepotential of this region for agricultural expansion, based on the model used for the Brazilian Cerrado. Thebasic materials were the rainfall data derived from the Tropical Rainfall Measuring Mission (TRMM),the digital elevation model obtained by the Shuttle Radar Topography Mission (SRTM) and the soiltexture data obtained from literature. Criteria used to identify potential areas of agricultural expansionin the Nacala Corridor were: slope ≤ 12%; and clayey or clay loamy soil textures. Approximately 82%,94% and 71% of the study area presented rainfall >1,000 mm, slope ≤ 12% and clayey or clay loamysoil textures, respectively. The potential area for agricultural expansion in the Nacala corridor was ~ 4.6million hectares. However, intensive agricultural occupation of this area needs to consider other aspectssuch as water pollution by chemical fertilizers, improvement of the human development index of localpeople and government regulations regarding the land use and land occupation in Mozambique.